2018
DOI: 10.1111/jocn.14151
|View full text |Cite
|
Sign up to set email alerts
|

Decision‐making in nursing practice: An integrative literature review

Abstract: Experienced nurses bring a broad range of previous patient encounters to their practice influencing their intuitive, unconscious processes which facilitates decision-making. Using naturalistic decision making as a conceptual framework to guide research may help with understanding how to better support less experienced nurses' decision-making for enhanced patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
212
1
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(241 citation statements)
references
References 53 publications
(174 reference statements)
16
212
1
12
Order By: Relevance
“…However, it was also noted that novice nurses struggled to differentiate between relevant and nonrelevant cues and this sometimes led to inappropriate responses (Burbach & Thompson, ). There have been similar findings in other studies related specifically to students' clinical decision‐making, for example Nibbelink and Brewer (). In this study, the researchers found that whilst students were able to discuss their decision‐making, the care they administered was reactive rather than proactive.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, it was also noted that novice nurses struggled to differentiate between relevant and nonrelevant cues and this sometimes led to inappropriate responses (Burbach & Thompson, ). There have been similar findings in other studies related specifically to students' clinical decision‐making, for example Nibbelink and Brewer (). In this study, the researchers found that whilst students were able to discuss their decision‐making, the care they administered was reactive rather than proactive.…”
Section: Introductionsupporting
confidence: 85%
“…However, they caution that there is limited evidence of effectiveness and trying to teach “more” does not equate to better performance. This may be related to students' limited practice experience and supports Nibbelink and Brewer's () hypothesis that experience was the largest influence on decision‐making. This is not to say that students should not be taught clinical decision‐making strategies but suggests that considerable work needs to be done to support students to make clinical decisions.…”
Section: Introductionsupporting
confidence: 77%
“…risk of suicidal intentionality recurrence/progression) or difficulties identifying problems at the borderlines between two or more established entities (i.e. differentiation between risk of infection recurrence/progression from risk of sepsis), so further studies are needed to gain a better understanding on this issue since, as long as there exist multiple levels of nurses' clinical expertise, different degrees of situation awareness capacity and clinical judgment accuracy will co‐exist (Nibbelink & Brewer, ).…”
Section: Discussionmentioning
confidence: 99%
“…The study presents those limitations implicitly embedded in a retrospective, cross-sectional, limited to a national level inquiry, whilst its multi-centre approach and large sample size are remark- (i.e. differentiation between risk of infection recurrence/progression from risk of sepsis), so further studies are needed to gain a better understanding on this issue since, as long as there exist multiple levels of nurses' clinical expertise, different degrees of situation awareness capacity and clinical judgment accuracy will co-exist (Nibbelink & Brewer, 2018).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation